Designing an approach for managing tacit knowledge in scrum-based software development teams in the Philippines - Agsaway, Franklin C. (University of the Philippines Diliman, 2012)
An approach for managing tacit knowledge in Scrum-based software development teams in the Philippines is presented based on identified gaps in four Scrum teams and applicable concepts and best practices in knowledge management that can be applied within the Scrum method.